Overcoming the Black Campaign as a Barriers to Democracy in the Era of Disruption of Information Technology with the Synergy of Bawaslu, the Minister of Communication and Information, and the Cyber Police Team (Law Research Review Quarterly, 2018)
2019 is a political year which is arguably the most important for the future of Indonesia where the Presidential and Vice President Elections will be held. One of the election problems that often surfaces is the Black Campaign or we are familiar with the term black campaign. The implementation of the black campaign is very influential in changing the culture of democracy in our country because this type of campaign is carried out to bring down other candidates with propaganda / lies. Black campaigns often use false news in the form of propaganda or popular with the term Hoax brought up by one political camp to another in order to reduce the credibility of a presidential candidate or vice presidential candidate who is put forward. As we know with the rapid pace of information technology at this time it is certainly very easy for unscrupulous persons who want to harm the noble value of democracy which is implemented in the principle of election principles and also of course it will be very influential in the understanding of politics in society in the following year. Certainly not only Bawaslu carries out the supervisory function. But Bawaslu in this case could have cooperated with the Minister of Communication and Information and the POLRI Cyber ​​Team to jointly overcome the existence of Hoaxes and other slanderous slanders that refer to one of the camps so that it tarnished the implementation of democracy.